2007
DOI: 10.1007/s00239-006-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ITS Ribosomal RNA Secondary Structures in Fungal and Algal Symbionts of Selected Species of Cladonia sect. Cladonia (Cladoniaceae, Ascomycotina)

Abstract: Evolutionary studies in lichen associations follow that of the fungal symbiont (mycobiont), which is the symbiont after which the lichen is named and forms the majority of the thallus. However, evolution of the algal partner (photobiont) is important to maintain compatibility between symbionts and to optimize productivity of the lichen association. The internal transcribed spacer (ITS) regions of the nuclear ribosomal DNA (rDNA) were examined for primary DNA sequence patterns and for patterns in the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 60 publications
3
32
1
Order By: Relevance
“…In contrast to this study, a study of ITS in ribosomal DNA in Cladonia mycobionts and associated photobionts indicated that Trebouxia strains clustered together according to geographical location and more closely corresponded to environmental features (e.g. soil type) than fungal lineages (Beiggi & Piercey-Normore, 2007). With the recently evolved basidiolichen Omphalina, Zoller and Lutzoni (2003) concluded that the Coccomyxa strain was genetically much more uniform than the mycobiont and distinct over a wide geographical range from cultures isolated from free-living populations and the strains found in lichens belonging to the Peltigeraceae.…”
Section: Evidence From Photobiont Molecular Analysiscontrasting
confidence: 73%
“…In contrast to this study, a study of ITS in ribosomal DNA in Cladonia mycobionts and associated photobionts indicated that Trebouxia strains clustered together according to geographical location and more closely corresponded to environmental features (e.g. soil type) than fungal lineages (Beiggi & Piercey-Normore, 2007). With the recently evolved basidiolichen Omphalina, Zoller and Lutzoni (2003) concluded that the Coccomyxa strain was genetically much more uniform than the mycobiont and distinct over a wide geographical range from cultures isolated from free-living populations and the strains found in lichens belonging to the Peltigeraceae.…”
Section: Evidence From Photobiont Molecular Analysiscontrasting
confidence: 73%
“…Therefore, structures that retain a highly conserved configuration may be useful tools for analyzing this cryptic species. 35 Using cytB sequences, we detected low values of intraspecific similarity (86-91%) and high values of nucleotide diversity (0.09-0.14) between the Phyllosoma complex species M. longipennis, M. mazzottii, T. mexicana, and M. picturatus from different geographic areas. For example, divergence levels for several T. infestans populations in South America did not exceed 2% 36 ; Within T. rubida populations from Mexico and the United States, the percentage similarity was 87%, and within the T. recurva population, the percentage similarity was 92%.…”
Section: Discussionmentioning
confidence: 86%
“…, , Cordeiro et al. , Nelsen and Gargas , Beiggi and Piercey‐Normore , Bačkor et al. , Kotelko and Piercey‐Normore , Škaloud and Peksa , Peksa and Škaloud , Řídká et al.…”
Section: Taxa Descriptionsmentioning
confidence: 99%